Update to the economic impact assessment of pillar one OECD/G20 Base Erosion and Profit Shifting Project - O'Reilly, Pierce (OECD Publishing, 2023)
This paper presents an update to the Economic Impact Assessment of Amount A of Pillar One of the Two Pillar Solution to Address the Tax Challenges Arising from the Digitalisation of the Economy. The revised assessment is based on Amount A as detailed in the text of the Multilateral Convention to Implement Amount A of Pillar One. With results extending from 2017 to 2021, the paper details the changes in the design of Amount A as well as updates to the data and methodology of the impact assessment. The paper outlines the impact of Amount A on the allocation of taxing rights and the resulting revenue impacts
Keywords: Taxation